2017
DOI: 10.1111/nan.12375
|View full text |Cite
|
Sign up to set email alerts
|

Ageing causes prominent neurovascular dysfunction associated with loss of astrocytic contacts and gliosis

Abstract: Strategies aimed to restore the loss of astrocytic end feet contact and reduce gliosis may improve neurovascular coupling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 48 publications
3
47
1
2
Order By: Relevance
“…Indeed, a study from the Nedergaard group demonstrated increased perivascular GFAP in aged (18 months) compared to young (2-3 months) C57BL/6 mice, coupled with a significant, but modest, loss of perivascular localization (Kress et al, 2014). A loss of vascular localization of AQP-4 has been demonstrated in old (24-months) compared to young (6-months) TgSwDI mice, which develop agedependent accumulation in amyloid, together with general reactive gliosis, as shown by increased number of GFAPpositive astrocytes and Iba 1-positive microglia (Duncombe et al, 2017). Preservation of perivascular localization of AQP-4 in aged human individuals was predictive of preserved cognitive abilities (Zeppenfeld et al, 2017).…”
Section: Aqp-4 In Aging and Alzheimer's Diseasementioning
confidence: 92%
“…Indeed, a study from the Nedergaard group demonstrated increased perivascular GFAP in aged (18 months) compared to young (2-3 months) C57BL/6 mice, coupled with a significant, but modest, loss of perivascular localization (Kress et al, 2014). A loss of vascular localization of AQP-4 has been demonstrated in old (24-months) compared to young (6-months) TgSwDI mice, which develop agedependent accumulation in amyloid, together with general reactive gliosis, as shown by increased number of GFAPpositive astrocytes and Iba 1-positive microglia (Duncombe et al, 2017). Preservation of perivascular localization of AQP-4 in aged human individuals was predictive of preserved cognitive abilities (Zeppenfeld et al, 2017).…”
Section: Aqp-4 In Aging and Alzheimer's Diseasementioning
confidence: 92%
“…Thus, consequences of cerebral hypoperfusion including myelin loss, severe loss of oligodendrocytes, activation of inflammatory processes and cognitive impairment were more severe in aged mice (Duncombe et al . ; Wolf et al . ).…”
Section: Contribution Of Laboratory Animal Studiesmentioning
confidence: 99%
“…Ageing exacerbates the effects to induce more severe WM degeneration and cognitive phenotypes. Thus, consequences of cerebral hypoperfusion including myelin loss, severe loss of oligodendrocytes, activation of inflammatory processes and cognitive impairment were more severe in aged mice (Duncombe et al 2016;Wolf et al 2017). While there could be an attempt for myelin replacement as suggested by increased number of immunolabelled NG2 cells even in old BCAS mice (Wolf et al 2017), these changes including the preservation of oligodendrocytes can be attenuated by environmental enrichment (EE) intervention more so by limited (3 h per day) rather than full-time exposure to EE .…”
Section: Contribution Of Laboratory Animal Studiesmentioning
confidence: 99%
“…During the ageing process, complex cellular and functional changes occur in the brain. These include neurovascular dysfunction manifesting in blood-brain barrier (BBB) breakdown associated with microscopic pathological changes of vascular cells 9,[18][19][20] . Forming the innermost lining of the vasculature, brain endothelial cells (ECs) closely interact with other cell types of the neurovascular unit (NVU) to regulate diverse functions including BBB integrity 8,12,13 , immune signaling and brain metabolism, all of which are altered in the aged brain 18,[21][22][23] .…”
Section: Introductionmentioning
confidence: 99%